TINJAUAN HUKUM USAHA BONGKAR MUAT BARANG DI PELABUHAN SAMARINDA BERDASARKAN PERATURAN PEMERINTAH NOMOR 20 TAHUN 2010 TENTANG ANGKUTAN DI PERAIRAN - Syamsuddin, Muhammad Hatta dan (Universitas 17 Agustus 1945 Samarinda, 2019)
Liability in sea transportation concerning loading and unloading of goodsis very important and is closely related to the rights and obligations of theparties. Therefore, separate regulations regarding sea transportation areneeded, both regulated by the international world and nationalregulations.One of the disputes that often arise in sea transportation is the damage togoods which raises the right of claim for compensation from the owner ofthe goods to the carrier. The emergence of claims from the owner of thegoods in the form of damage to the goods, it is important to pay attentionto the parties involved in the transportation process to be able todetermine which party is really responsible for claims for compensationfor damage to the goods.The purpose of this study is to determine the implementation of loadingand unloading of goods carried out in the Port of Samarinda and todetermine the responsibility of employers for losses incurred in theprocess of loading and unloading at the Port of Samarinda.The study uses normative juridical research methods and techniquesnamely library research and document research.The results of this study are (1) The loading and unloading business atports as an integral part of the port management system in Indonesia isstated in PP No. 2 of 2010 concerning Transportation on Water. Based onthis PP, loading and unloading activities from and to ships are carried outby shipping companies through the loading and unloading business units.(2) In Article 180 Paragraph 1 states that the transport company in thewater transport company is responsible for the safety and security of thepassengers and / or the goods they transport. Then Article 180 Paragraph2 states that the water transport company is responsible for the cargo ofthe ship in accordance with the type and amount stated in the cargo document and / or the agreed transportation agreement or contract. Thisform of protection is intended to protect and maintain the integrity andsecurity of transported goods during loading and unloading activities